Romantic beliefs and myths in Spain. - Martínez-íñigo, David; Paúl, Pilar de; Barrón, Ana; Yela, Carlos (The Spanish Journal of Psychology, 1999)
Sin resumen
Keywords: mitos románticos; sexo; amor; matrimonio